Tailoring the Optical Absorption of Water‐Stable ZrIV‐ and HfIV‐Based Metal–Organic Framework Photocatalysts. Issue 12 (4th September 2015) - Doan, Tan L. H.; Nguyen, Ha L.; Pham, Hung Q.; Pham‐Tran, Nguyen‐Nguyen; Le, Thach N.; Cordova, Kyle E.
Abstract: New Zr IV ‐ and Hf IV ‐based metal–organic framework photocatalysts, termed VNU‐1 and VNU‐2 (where VNU=Vietnam National University), were synthesized and their resulting structures fully characterized. By employing a highly π‐conjugated linker, namely 1, 4‐bis(2‐[4‐carboxyphenyl]ethynyl)benzene, the optical absorption properties were effectively red‐shifted into the visible light region. This strategy, coupled with the high water stability of the materials, led to enhanced MOF‐driven photocatalytic degradation, under ultraviolet‐visible light, of organic dye pollutants commonly found in wastewater. Abstract : It is so degrading : The optical absorption of a new water‐stable zirconium‐based metal–organic framework was effectively red‐shifted due to the use of a highly π‐conjugated linker backbone. This led to enhanced photocatalytic activity in the degradation of organic dye molecules, and the heterogeneous nature of the photocatalyst was proven by the recyclability of the material.